(untitled) (BIRDEM Medical Journal, 2020)
Background: Fetal iron stores are affected by maternal diabetes and it is lower at birth in infants of diabetic mothers (IDMs). Risks for developing iron deficiency and neurocognitive impairment are reported in IDMs. This study was done to assess serum ferritin and red cell indices in IDMs and to compare the values with infants born to mothers without diabetes mellitus. Methods: This cross-sectional study was carried out at BIRDEM General Hospital from March to October, 2018. Total 102 full term neonates were included in this study. Among them 70 neonates were IDMs and 32 were infants born to mother without diabetes mellitus. Serum ferritin and red cell indices like hemoglobin (Hb), packed cell volume (PCV), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), red cell distribution width (RDW) were measured within 48 hours of birth. Comparison of red cell indices and serum ferritin level were done between IDMs and infants of non-diabetes mothers. Statistical analysis was performed by using Epi info, and p value of <0.05 was considered statistically significant. Results: IDMs had significantly higher value of Hb% (19.00 vs 17.47 g/dl), PCV (57.60 vs 52.67 %) and RDW (20.09 vs17.77 %) than infant of non-diabetic mother (p <0.05). But there was no significant difference regarding the values of MCV, MCH and MCHC between IDMs and infants of non-diabetic mothers (p >0.05). Serum ferritin level was found significantly low in IDMs (94.51 vs 307.50 ng/ml, p <0.001). Conclusion: Iron stores of IDMs were found significantly lower at birth despite higher hemoglobin content, as indicated by lower serum ferritin level. Further studies and long-term follow up are needed to determine whether these infants are at risk for developing iron deficiency anemia or iron-deficient neurocognitive disorder Birdem Med J 2020; 10(3): 182-186